Constraints perceived by the dairy farmers about fodder production in Rajasthan state of India - meena, devendra kumar (Indian Journal of Dairy Science, 2017)
The present study was conducted in Rajasthan. The investigation concerned with Semi-arid zone of Rajasthan, which is the highest livestock and bovine population in zone, 6986.2 and 3287.9 thousands; respectively. Milk production and productivity depend on the quality and quantity of feed & fodder. Feed & fodder constitute about 60-70 per cent cost of milk production. A portion of its fodder requirement is also met by lopping and cutting of trees from the agricultural fields and homestead areas. It was estimated that major consumption of crop residue and green fodder varies in different seasons. This feed resource, which consists mainly of grasses, legumes and cereal crop residues vary widely and are spread across the major agro- ecological zones of the Rajasthan. Hence, an investigation entitled â€œA Comprehensive Study on Fodder Production and Its Utilization Pattern in Semi-Arid Zone of Rajasthanâ€ was conducted on proportionate randomly selected 240 dairy farmers of Dausa and Tonk districts in Semi- arid zone of Rajasthan.